FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR SISWA DALAM MENGIKUTI PELAKSANAAN BELAJAR TUNTAS - Minarti Minarti; Berchah Pitoewas; Hermi Yanzi (FKIP Unila, 2015)
The focus of this research is to analyze and explained the factors causing student learning difficulties in following the implementation of Mastery Learning. This research using methods descriptive qualitative with a population of 155 respondents so samples taken as many as 20% of respondents namely 31. Based on the results show that the research: (1) Indicators motivation as many as 45,16% of respondents is categorized as a motivation was. (2) Indicators teachers as many as 48,39% of respondents is categorized as a very influential. (3) Indicators of facilities and infrastructure as many as 70,97% of respondents is categorized as a little influence. (4) Indicators speed learn as much as 58,06% of respondents is categorized as a learning was speed. (5) Indicators as much time as 48,39% of respondent is categorized as a very influential. So it can be concluded that the implementation of work completed in still learning to be optimized to a learning disability students be handled.Fokus penelitian ini adalah untuk mengalisis dan menjelaskan faktor-faktor penyebab kesulitan belajar siswa dalam mengikuti pelaksanaan belajar tuntas. Penelitian ini menggunakan metode deskriptif kualitatip dengan jumlah populasi 155 responden, sehingga sampel yang diambil sebanyak 20% yaitu 31 responden. Berdasarkan hasil penelitian menunjukan bahwa: (1) indikator motivasi sebanyak 45,16% responden masuk kategori motivasi sedang. (2) Indikator guru sebanyak 48,39% responden masuk kategori sangat berpengaruh. (3) Indikator sarana dan prasarana sebanyak 70,97% responden masuk kategori kurang berpengaruh. (4) Indikator kecepatan belajar sebanyak 58,06% responden masuk kategori kecepatan belajar sedang. (5) Indikator waktu sebanyak 48,39% reponden masuk kategori sangat berpengaruh. Jadi dapat disimpulkan bahwa penerapan belajar tuntas masih perlu dimaksimalkan agar kesulitan belajar siswa dapat teratasi.Kata kunci : belajar tuntas, kesulitan belajar, siswa.